Study of polarized wave with a hydrodynamic model and Fourier spectral method - Ching, D.L.C. (Hindawi Limited, 2013)
The polarization effects in hydrodynamics are studied. Hydrodynamic equation for the nonlinear wave is used along with the polarized nonlinear waves and seismic waves act as initial waves. The model is then solved by Fourier spectral and Runge-Kutta 4 methods, and the surface plot is drawn. The output demonstrates the inundation behaviors. Consequently, the polarized seismic waves along with the polarized nonlinear waves tend to generate dissimilar inundation which is more disastrous. Â© 2013 Dennis Ling Chuan Ching et al.